1999
DOI: 10.3141/1689-09
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Networkwide Effects of Variable Message Signs in the Netherlands

Abstract: The use of variable message signs (VMSs) is generally considered to be a powerful tool to influence route choice so as to increase safety and comfort during driving and improve network performance and to make optimum use of available capacity. Assessing whether such effects actually occur when VMSs are installed is a difficult task. This paper summarizes an extensive evaluation study carried out on the installation of 14 new VMSs on the Amsterdam orbital motorway. The study involves a number of issues. First, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…In addition, other studies applied fuzzy logic principles like ''if-then'' rules (Peeta and Yu 2005;Lotan 1993) or dynamic assignment and micro simulation using artificial agents (Nakayama et al 2001;Nakayama and Kitamura 2000;Nakayama et al 1999;Bonsall et al 1997). A few studies attempted to investigate information impacts using revealed preference field studies of real locations or ATIS systems (Fujii and Kitamura 2000;Kraan et al 1999;Deakin 1997;Wardman et al 1997;Khattak and Khattak 1996). The current study is designed to contribute to this line of empirical research by building on recent basic behavioral research.…”
Section: Introductionmentioning
confidence: 94%
“…In addition, other studies applied fuzzy logic principles like ''if-then'' rules (Peeta and Yu 2005;Lotan 1993) or dynamic assignment and micro simulation using artificial agents (Nakayama et al 2001;Nakayama and Kitamura 2000;Nakayama et al 1999;Bonsall et al 1997). A few studies attempted to investigate information impacts using revealed preference field studies of real locations or ATIS systems (Fujii and Kitamura 2000;Kraan et al 1999;Deakin 1997;Wardman et al 1997;Khattak and Khattak 1996). The current study is designed to contribute to this line of empirical research by building on recent basic behavioral research.…”
Section: Introductionmentioning
confidence: 94%
“…For example, the Flemish authorities are currently reconstructing and storing the daily travel times on their entire highway network. Initiatives like this are necessary to monitor the performance year after year and to evaluate traffic managing implementations that influence accessibility and travel time reliability (Chen, Yang, Lo, & Tang, 2002;Chen, Skabardonis, & Varaiya, 2003;Kraan, van der Zijpp, Tutert, Vonk, & van Megen, 1999). A second use of offline travel times is for calibrating travel and traffic models (Ashok, 1996;Cipriani, Florian, Mahut, & NIgro, 2010).…”
Section: Overview Of Travel Time Estimatorsmentioning
confidence: 99%
“…Emmerink et al (1996) and Bonsall and Palmer (1999) conclude that good driver compliance cannot necessarily be assumed. Kraan et al (1999) conclude that VMSs significantly influence route choice, thereby decreasing total congestion and increasing travel time reliability by reducing the variance of travel times and congestion.…”
Section: Introductionmentioning
confidence: 96%